(untitled) - Weinstein, Carol Simon (London, 2007)
Tressing the need to build caring, supportive relationships with and among students, Middle and Secondary Classroom Management: Lessons from Research and Practice offers research-based guidance on effective classroom management. It addresses current concerns about student motivation and helps prospective and beginning teachers develop a philosophy of classroom management that focuses on building connections with students and creating safe, caring classrooms. By integrating the thinking and the actual management practices of four real secondary teachers into discussions of research-based management principles, this introductory text helps readers connect theories with actual results. Further, the text demonstrates how real teachers can adapt to any circumstance--physical room constraints, curriculum requirements, challenging behaviors--and still be successful.
Keywords: Quản lý lớp học,Giáo dục, Cấp hai,Classroom management,Education, Secondary,Education, Elementary